Economic Survey of Latin America and the Caribbean 2002-2003 - Economic Commission for Latin America; the Caribbean (United Nations, 2003)
The present edition of the Survey consists of three parts. The first part covers the main aspects of the regional economy from a sectorial and thematic perspective. The second part contains information of the analysis of the economic performance of the 19 countries of Latin America and the Spanish-speaking Caribbean and Haiti. The third part is dedicated to the remaining countries of the Caribbean, mainly English-speaking countries. Finally, the Survey offers two statistical appendixes, one of them contained in a CD-ROM distributed with the printed version.